PERSEPSI KONSUMEN TERHADAP PRODUK OLAHAN IKAN TENGGIRI DI KABUPATEN SAMBAS - Dian Sari (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
One way to determine consumer behavior is to analyze their perceptions of the product. With consumer perception, producers can find out what are the strengths or weaknesses, opportunities or threats for the products being marketed. This study aims to determine how consumers' perceptions of processed mackerel fish products in Kabupaten Sambas. The method used in this research is a survey method. The number of respondents studied were 100 people, using incidental sampling. The analysis design used is descriptive analysis. The results of the study revealed that overall consumer perceptions of processed mackerel, namely consumer perceptions of the price of processed mackerel fish products obtained a score of 413 with an average value of 4,13 (strongly agree,) Consumer perceptions of the quality of processed mackerel fish products obtained a score of 412 with an average -average 4,00 (agree), consumer perceptions regarding the availability of processed mackerel fish products get a score of 402 with an average score of 4,00 (agree). average 4,04 (strongly agree).